The Nature of the Relationship between Customers and Suppliers of Language Teaching Services in the Business Community: A Case Study of MNMC - Sargunan, Rajeswary A. (Journal of Modern Languages, 2017)
This study mentions that the nature of the relationship is dictated by the goals, expectations, assumptions and attitudes of the various participants within the ecosystem with regard to each other. The study also shows that the relationship is characterized by vagueness and uncertainty. In order for any learning to be effective, it is necessary that the participants in the learning encounter come to it with clearly defined goals and attitudes so that an effective strategy can be devised to attain these goals.